On Fibrewise star topological spaces - Najia Mohammed Alsharrani (African Journal of Advanced Pure and Applied Sciences, 2025)
This paper introduces fibrewise star topological spaces, a new concept in fibrewise topology. We explore their fundamental properties and connections to modern applications, such as adaptive network systems. By studying projections and neighborhood structures in these spaces, we establish key theoretical results while demonstrating their potential for modeling multi-domain problems. The work bridges abstract topology with practical computational frameworks, offering a foundation for future research in compactness, connectedness, and real-world implementations.